Rotational performance of frictional glulam beam-to-column connections with shape memory alloy strips. (January 2022) - Wu, Ya-Jie; Xie, Qi-Fang; Zhang, Yi; Zhang, Li-Peng; Yang, Hui-Feng
Abstract: Resilience has becoming a favorable direction in developing structures against various hazards especially earthquakes. In order to promote structural maintainability and enhance self-centering effect of heavy timber structures, this paper proposed frictional glulam beam-to-column connections (FCs) with shape memory alloy (SMA) strips and experimentally investigated their rotational performance. Four half-scaled FCs with SMA strips, characterized by flat and pyramid frictional timber pads, were cyclically tested considering different loading rates, and compared with a conventional glulam beam-to-column connection (CC) at multi loading amplitude levels. The test results showed that FCs with SMA strips were damage-free in vulnerable connection zones, except part of SMA strips failed in tension but could be easily replaced. The hysteretic behavior of FCs with SMA strips was insensitive to loading rate, indicating a consistent and stable performance. Compared to those of CC, the initial stiffness of FCs with SMA strips did not significantly change, although the peak moments decreased 15%–30%, the energy dissipation capacity was increased roughly 100% and less residual deformation was obtained owning to friction mechanism and pesudoelasticity of SMA. Numerical study was further conducted to illustrate the benefits by applying the proposed connections in framed structures. It is found that adopting FCs with SMA strips instead of CCs would not considerably change the dynamic response of timber frames under minor earthquakes, but would significantly reduce the maximum story drift and residual drift of structures under strong earthquakes. Although the type of frictional timber pads had slight influence on the rotational performance of FCs with SMA strips, this influence was negligible in structural level. Highlights: Frictional glulam beam-to-column connections with shape memory alloy strips were proposed. High maintainability and superior energy dissipation capacity of the proposed connections were experimentally verified. Numerical analysis was conducted in structural level to illustrate the benefits of adopting the proposed connections.